Part 1 - imidazolines and the changing face of nasal decongestants - Stinson, Rebecca J.; Sadofsky, Laura R. (Frontiers in Pharmacology, 2025)
Imidazolines are sympathomimetic drugs used to treat a range of conditions including nasal congestion, ocular disorders, and hypertension. Imidazolines were discovered over 150 years ago. However, it was research from the 1940s onwards which established the therapeutic benefits of imidazolines. Although there is extensive literature describing imidazolines, the history and timeline of their development is not well documented. This review focuses on the evolution of imidazoline pharmacology particularly those used in nasal decongestants, naphazoline, tetrahydrozoline, xylometazoline and oxymetazoline. These derivatives activate the α1-and α2-adrenergic receptors with varying degrees of selectivity, to provide decongestive relief through vasoconstriction. This reduces swelling of the nasal mucosa, delivering both subjective and objective relief from congestion. Each new imidazoline derivative has improved onset and duration of action, resulting in treatments with enhanced efficacy, tolerability, and safety. Although these advancements allow for less frequent dosing with comparable effects, the importance of correct usage for optimal benefit cannot be overstated. These nasal decongestants are considered safe when used as recommended however, rhinitis medicamentosa, characterized by chronic nasal congestion, can occur with excessive use. Imidazolines are an important class of compounds which have shown improvements in efficacy and safety over time. However, further improvements could be made with more advances in understanding their pharmacology.